PENGARUH FINANCIAL LEVERAGE, INVESTASI, LIKUIDITAS, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Meithasari, Dian; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
A company sets earning policy to manage its earning which allocated to two components namely dividend and retained earning. Dividend is a part of earning available for stockholders. Retained earning is a part of earning retained to be reinvested for growing the company. The purpose of this research is to understand the way financial leverage, investment, liquidity, and profitability influence the company’s dividend policy. This is an explanatory research, using 19 manufacturing companies listed in Indonesian Stock Exchange from 2008 up to 2010 as samples. Type of data that is used in this research is panel data and quantitative data from secondary source. This research uses double linear regression analysis by SPSS test considering the classic assumption test, namely normality, multicollinearity, heterocedastity, and autocorelation, continued with hypothesis test, namely F test and t test. Result shows that financial leverage, investment, liquidity, and profitability don’t give significant impact on dividend policy simultaneously and partially.